2019
DOI: 10.1016/j.heliyon.2019.e02591
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and risk assessment of heavy metals, and uranium of sediments in two watersheds in Abiete-Toko gold district, Southern Cameroon

Abstract: In this investigation, the level of toxic metals (Cd, Pb, Hg, Cu, Ni, Al, Zn and U) was determined in sediment samples from two watersheds (Kienké and Tchangué) in the Abiete-Toko gold district, southern Cameroon. The potential contamination and toxicity of studied metals was determined by evaluating enrichment factor (EF), geo-accumulation index (Igeo) and ecological risk assessment (ERA). Considering the spatial distribution patterns, metal concentrations were lower than the average shale values, except for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 59 publications
(86 reference statements)
0
48
1
1
Order By: Relevance
“…Although the carcinogenic risk index was ranged from 1.46 * 10 −6 to 232.62 * 10 −6 and target hazard quotient (THQ) was varied from 0.0036 to 1.08, rigorous monitoring of source and overall effective management is necessary to control notorious fate and transport of the above mention metals. Mandeng et al (2019) used enrichment factor (EF), geo-accumulation index (I geo ), ecological risk index (ERI), and pollution load index (PLI) to identify the contamination level and risk potential of sediments after analyzing 13 composite samples from two watersheds, that is, Kienké and Toko contaminated by heavy metals and uranium (U) in Southern-Cameroon where average metal concentrations were within the range of 8,501.08-9,590.01 (Al), 0.099-0.128 (Cd), 5.85-5.976 (Pb), 0.068-0.106 (Hg), , and 0.534-0.78 mg/kg (U). Although the watersheds were moderately enriched by heavy metals and U with very high ER factor, the sites were considered as unpolluted.…”
Section: Toxicological Risk Assessmentmentioning
confidence: 99%
“…Although the carcinogenic risk index was ranged from 1.46 * 10 −6 to 232.62 * 10 −6 and target hazard quotient (THQ) was varied from 0.0036 to 1.08, rigorous monitoring of source and overall effective management is necessary to control notorious fate and transport of the above mention metals. Mandeng et al (2019) used enrichment factor (EF), geo-accumulation index (I geo ), ecological risk index (ERI), and pollution load index (PLI) to identify the contamination level and risk potential of sediments after analyzing 13 composite samples from two watersheds, that is, Kienké and Toko contaminated by heavy metals and uranium (U) in Southern-Cameroon where average metal concentrations were within the range of 8,501.08-9,590.01 (Al), 0.099-0.128 (Cd), 5.85-5.976 (Pb), 0.068-0.106 (Hg), , and 0.534-0.78 mg/kg (U). Although the watersheds were moderately enriched by heavy metals and U with very high ER factor, the sites were considered as unpolluted.…”
Section: Toxicological Risk Assessmentmentioning
confidence: 99%
“…The volume of this waste rock resulting from the sinking process often depends on the depth at which this level is located. This depth often varies from a few meters to more than ten meters [15,36]. When the depth of the pit becomes significant, the stripping is done in successive steps (Figure 4b) and the different levels of the ground thus stripped are placed on these bearings for easy evacuation.…”
Section: Destruction Of Vegetation Covers (Deforestation)mentioning
confidence: 99%
“…Gold mining could also be the cause of soil infertility, as a result of the erosion of the organo-mineral layer. The soils are then destroyed, and therefore not suitable for agriculture ( Figure 4d) [36][37][38].…”
Section: Destruction Of Vegetation Covers (Deforestation)mentioning
confidence: 99%
See 1 more Smart Citation
“…and radionuclides (e.g., U, Th, Ra, etc.) in mining ecosystems have been widely reported [17][18][19][20]. Radionuclides pollution and toxic metals loading in shallow tailings, discharge water, surface water, groundwater, and paddy soil around the study uranium mining area were found and recognized [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%